2016
DOI: 10.22374/cjgim.v10i4.90
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Four Limb Compartment Syndrome

Abstract: SummaryWe present a unique case of atraumatic rhabdomyolysis and four-limb compartment syndrome. Edema and inflammation associated with rhabdomyolysis, was further exacerbated by aggressive saline resuscitation. This resulted in raised compartment pressures and necessitated four-limb fasciotomy. The cause of rhabdomyolysis was most likely multifactorial including systemic capillary leak syndrome seizure, illicit drug use (crack cocaine and methamphetamine) and the prescription medication, mirtazapine. RésuméNo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Riolo et al in 2015 have reported a case of four-limb compartment syndrome in 49-year-old with a history of hepatitis B, chronic hepatitis C, and epilepsy; the patient developed four-limb compartment syndrome, and they concluded that it was due to rhabdomyolysis caused by multiple factors, the patient underwent urgent four-limb fasciotomy. [7] Also, Khan et al had reported a similar case (only in one limb) of 41-year-old medically free lady who suffered from rhabdomyolysis and acute renal failure simultaneously, and the cause was attributed to inadvertent posturing while sleeping. [8] The patient developed bilateral spontaneous compartment syndrome in the leg, which was treated by fasciotomy.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Riolo et al in 2015 have reported a case of four-limb compartment syndrome in 49-year-old with a history of hepatitis B, chronic hepatitis C, and epilepsy; the patient developed four-limb compartment syndrome, and they concluded that it was due to rhabdomyolysis caused by multiple factors, the patient underwent urgent four-limb fasciotomy. [7] Also, Khan et al had reported a similar case (only in one limb) of 41-year-old medically free lady who suffered from rhabdomyolysis and acute renal failure simultaneously, and the cause was attributed to inadvertent posturing while sleeping. [8] The patient developed bilateral spontaneous compartment syndrome in the leg, which was treated by fasciotomy.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, this, in turn, may lead to a closed cycle of increasing edema, and more muscle damage and necrosis. [7] Dalton et al described a case of acute spontaneous compartment syndrome in both forearms in a 31-year-old lady with no history of trauma presented to the ED with acute compartment syndrome in the forearm. Her past medical history was only positive for hypertension and coeliac disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compartment syndrome is a surgical emergency with multiple traumatic and nontraumatic causes [1]. There have been reports of uncommon multiple conditions leading to acute compartment syndrome outside the scope of trauma such as diabetes mellitus, hypothyroidism, leukemia infiltration, nephrotic syndrome, rhabdomyolysis, and the use of anticoagulation [2][3][4][5]. The relation between tibia shaft fracture and compartment syndrome has been well established in the literature, and the gold standard treatment of such a fracture is intramedullary nail fixation with surgical decompression of the leg compartments [6,7].…”
Section: Introductionmentioning
confidence: 99%